1999
DOI: 10.1002/(sici)1521-4141(199908)29:08<2436::aid-immu2436>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Normal human immunoglobulin suppresses experimental myasthenia gravis in SCID mice

Abstract: Serum IgM has been shown to participate in the control of IgG autoreactivity in healthy subjects. We have recently shown that an immunoglobulin preparation of pooled normal human IgM (IVIgM) contains anti-idiotypic antibodies against disease-associated IgG autoantibodies in autoimmune patients and protects rats from experimental autoimmunity. The aim of the present study was to asses the in vitro and in vivo immunomodulatory effects of IVIgM in comparison with IgG, in SCID mice reconstituted with thymic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…The very same preparation of polyclonal human IgM used in this study has been demonstrated to neutralize autoantibodies (28) and alter cytokine expression in experimental autoimmune encephalomyelitis (44) and to be beneficial in a mouse model of myasthenia gravis (45). Polyclonal human IgM, but not IVIg, binds to myelinated tracts in unfixed slices of rodent brain.…”
Section: Discussionmentioning
confidence: 90%
“…The very same preparation of polyclonal human IgM used in this study has been demonstrated to neutralize autoantibodies (28) and alter cytokine expression in experimental autoimmune encephalomyelitis (44) and to be beneficial in a mouse model of myasthenia gravis (45). Polyclonal human IgM, but not IVIg, binds to myelinated tracts in unfixed slices of rodent brain.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, the activation-induced cytidine deaminase-deficient MRL-lpr mice that lack IgG but have increased autoreactive IgM do not develop lupus nephritis (29). There are also reports that administration of IgM has beneficial effects in some experimental autoimmune models (30,31). By analyzing a lupus patient's sera against a multiplex autoantigen microarray, Mohan and colleagues (32) have found that the presence of IgM polyreactivity is correlated with reduced disease severity.…”
mentioning
confidence: 99%
“…Reduced antibody responses to the autoantigen have been reported in other experimental autoimmune diseases in which effective IVIG treatment has been demonstrated, such as experimental autoimmune myositis, experimental autoimmune myocarditis, 10,11 and an experimental murine model of systemic lupus erythematosus 13 . There has also been a report showing that pretreatment by IVIGM reduced serum anti‐AChR antibodies in myasthenic SCID mice reconstituted with thymic cells from a myasthenia gravis patient 19 …”
Section: Resultsmentioning
confidence: 88%
“…IVIG has been employed to treat MG for about two decades 14–17 and was shown to be effective in MG on a long‐term basis without significant side effects 18 . In a SCID mouse model of human MG it has been demonstrated that pretreatment with IVIG and intravenous IgM (IVIGM) decreased the production of anti‐AChR antibodies in the serum and led to a decreased loss of endplate AChR in the diaphragms of treated mice 19 …”
Section: Introductionmentioning
confidence: 99%